Analisis Kompetensi Sumber Daya Manusia Dalam Menghadapi Era Industri 4.0 - Matondang, Zulfadli Prawira (Universitas Labuhanbatu, 2024)
In the era of globalization, the problem of human resources is a focus for both government and private organizations. Human resources is a valuable asset or property owned by an organization. In achieving this success, a strong foundation is needed such as human resources who have competencies such as hardskill or softskill. This competence also includes knowledge, skills, and attitudes that are key components in management and become strategic in improving employee performance. management and Human Resources. Management means directing and encouraging HR to work as a partner in achieving the success of the company in the present and the future. Besides that, it can be said that the definition of Human Resource Management, is a way of how to regulate the relationship and role of human resources (labor) owned by individuals who are managed by HR professionals and managers so that 5 M can be managed efficiently and effectively and can be used optimally to achieve the goal (goal). Management has a function called the management functions function to manage 6 M namely: Man, Machine, Material, Money, method and Market. Man is a human or human resources that serves to manage the other 5 M .